A low-shrinkage, high-toughness polylactic acid composite material and preparation method thereof
By using dynamic bond-containing polysulfides and polyfuran groups-containing compounds as crosslinking agents, dynamic crosslinking technology prepares high-toughness polylactic acid composites, solving the problems of toxic volatiles and permanent crosslinking structures in the prior art, and achieving high-efficiency toughening and low shrinkage.
Patent Information
- Application Number
- CN202310195319.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-03
AI Technical Summary
There are toxic and harmful volatiles in the existing polyurethane toughened polylactic acid technology, and the rubber phases in the highly tough polylactic acid composite materials are mostly permanent crosslinked structures, which limits their application.
Using dynamic bond-containing polysulfides and polyfuran groups-containing compounds as crosslinking agents, a high toughness polylactic acid composite material with low shrinkage is prepared through dynamic crosslinking technology, combining a mixture of polylactic acid, polyurethane and/or its reaction products.
It has achieved dynamic cross-linked polyurethane toughened polylactic acid with good toughening effect and low green environmental hazards. The notch impact strength can reach 99.38KJ/m2, and at the same time, it reduces the shrinkage rate of the composite material, which is suitable for precise processing.
Smart Images

Figure CN116376244B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a high-toughness polylactic acid composite material with low shrinkage and a preparation method thereof. Background Art
[0002] As a bio-based degradable plastic, polylactic acid can effectively solve the white pollution problem caused by the non-degradable traditional plastics. However, the shortcomings of polylactic acid such as high brittleness and easy fracture greatly limit its application. In view of the shortcomings of low toughness of polylactic acid itself, researchers at home and abroad have carried out a lot of work on the research direction of polylactic acid toughening. The current research mainly focuses on chemical copolymerization modification, physical blending modification, dynamic vulcanization modification, etc.
[0003] The notched impact strength of polylactic acid composites after dynamic vulcanization toughening of natural rubber (Chinese patent CN107459793A) or modified natural rubber (Chinese patent CN109401243A) can reach 70kJ / m 2 , showing a good toughening effect. However, the adjustable range of traditional rubber materials is limited, while polyurethane elastomers are highly designable and are good alternative materials. At present, polyurethane materials are often toughened by excessive isocyanate dynamic vulcanization technology on polylactic acid, and a significant toughening effect has been achieved (such as Chinese patents CN108707322A and CN103450649A).
[0004] The main problems existing in the existing polyurethane toughened polylactic acid technology are: 1. The process contains toxic and harmful volatiles, which endanger the health of operators; 2. The rubber phase in the high-toughness polylactic acid composite material is mostly a permanent cross-linked structure. Summary of the invention
[0005] In view of the problems existing in the existing technical solutions, the main purpose of the present invention is to provide a technical solution of dynamically cross-linked polyurethane toughened polylactic acid with good toughening effect and little environmental harm. At the same time, the technical solution of the present invention is matched with existing industrial equipment and has a high prospect for industrial application.
[0006] One of the objects of the present invention is to provide a low shrinkage and high toughness polylactic acid composite material, comprising: a mixture of polylactic acid, polyurethane, a cross-linking agent and / or its reaction product, wherein the cross-linking agent is at least one of a polysulfide containing dynamic bonds and a compound containing polyfuran groups.
[0007] Wherein, the dynamic bond in the polysulfide containing dynamic bonds is at least one of a dithioacetal bond, a disulfide bond, an imine bond, a β-hydroxy ester bond, a boric ester bond, a silyl ether bond, and a cyclic acetal bond;
[0008] In the polyurethane, the hard segment content is 10 to 50 wt%, preferably 20 to 30 wt%; the R value is 1.00;
[0009] Taking the total amount of the high-toughness polylactic acid composite material as 100wt%, the content of the polyurethane is 5-50wt%, preferably 7-50wt%;
[0010] Based on 100 wt% of the total amount of the polylactic acid and the polyurethane, the amount of the crosslinking agent is 0.01 to 12 wt%, preferably 0.15 to 10 wt%.
[0011] In the polylactic acid composite material provided by the present invention, the polysulfide containing dynamic bonds is the reaction product of an aldehyde compound and a polythiol compound, wherein the aldehyde compound is selected from at least one of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, succinaldehyde, terephthalaldehyde, and trimesic acid; and the polythiol compound is selected from at least one of ethanedithiol, propylenethiol, butanedithiol, 1,2,4,5-tetramercaptobenzene, pentaerythritol tetrakis(2-mercaptoacetic acid), pentaerythritol tetrakis(3-mercaptopropionic acid), and hexamercaptotriphenylene.
[0012] In the polylactic acid composite material provided by the present invention, the compound containing a polyfuran group is selected from at least one of 2,2'-difuranmethane and 2,2'-(1,3-propylenediyl)difuran.
[0013] In the polylactic acid composite material provided by the present invention, the polyurethane is the reaction product of a macromolecular polyol, an isocyanate compound, and an unsaturated chain extender, wherein:
[0014] The macromolecular polyol is selected from at least one of polyester polyols, polyether polyols, polyolefin polyols, polysiloxane polyols, or derivatives thereof, preferably non-bio-based polyester polyols (polycaprolactone, polypropylene glycol, polyethylene glycol, polybutylene adipate, polypropylene adipate, polyethylene adipate, polypropylene succinate, polyethylene succinate, etc.) or bio-based polyester polyols (Priplast 3197, Priplast 3238, Priplast 3294, etc.), non-bio-based polyether polyols (polytetrahydrofuran, polyethylene glycol, polypropylene glycol, etc.) or bio-based polyether polyols (polytrimethylene ether glycol, pripol 2033, etc.), non-bio-based polyolefin polyols (terminated hydroxy butylbenzene polyols, terminal hydroxy butadiene polyols, etc.) or bio-based polyolefin polyols (polyfarnesene polyols, etc.), polysiloxane polyols; the number average molecular weight of the macromolecular polyol is 500 to 4000, preferably 1000 to 2000;
[0015] The isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, dimethyl biphenyl diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, methylcyclohexyl diisocyanate, pentamethylene diisocyanate, lysine diisocyanate, polymethylene polyphenyl isocyanate, and toluene diisocyanate dimer, preferably at least one of pentamethylene diisocyanate and hexamethylene diisocyanate;
[0016] The unsaturated chain extender is selected from at least one of small molecule diols with unsaturated carbon-carbon double bonds, preferably at least one of α-allyl glycerol ether and trimethylolpropane monoallyl ether;
[0017] An antioxidant is also added to the polyurethane. Preferably, the antioxidant is selected from at least one of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate] (Kang 245), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] (Kang 1010), and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl) benzene (Kang 1030).
[0018] The second object of the present invention is to provide a method for preparing the above-mentioned low shrinkage high-toughness polylactic acid composite material, comprising: adding polylactic acid to polyurethane after melting and mixing evenly, adding a crosslinking agent, and melt blending to obtain the low shrinkage high-toughness polylactic acid composite material; wherein the melt blending conditions are: the melting temperature is 165-200°C, and the melting time is 5-30min. The high-toughness polylactic acid composite material can be obtained by the following preparation process: adding the dried polylactic acid to an internal mixer at 165-200°C and 30-200 rpm for 2-5 minutes; adding the cured and dried unsaturated polyurethane to the internal mixer, at 50-200 rpm, melt mixing for 2-5 minutes; adding a crosslinking agent containing a dynamic bond, at 100-200 rpm, melt mixing for 5-30 minutes and then taking it out.
[0019] Wherein, the polyurethane is prepared by the following method:
[0020] Method 1: Prepolymerize a macromolecular polyol and an isocyanate compound under the action of a catalyst, then add an unsaturated chain extender to carry out a chain extension reaction, and obtain the polyurethane after curing; or,
[0021] Method 2: stirring and reacting a macromolecular polyol, an isocyanate compound and an unsaturated chain extender under the action of a catalyst, and curing the resultant to obtain the polyurethane.
[0022] In the preparation method of the above polyurethane:
[0023] The catalyst is selected from at least one of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst, preferably at least one of stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, di(dodecylthio)dibutyltin, zinc isooctanoate, and bismuth isooctanoate;
[0024] The amount of the catalyst is 0.01 to 0.5 wt% of the total amount of the macromolecular polyol, isocyanate compound and unsaturated chain extender;
[0025] An antioxidant is also added to the reaction. Preferably, the amount of the antioxidant is 0.01 to 0.5 wt% of the total amount of the macromolecular polyol, isocyanate compound and chain extender.
[0026] Based on 1 mole of the macromolecular polyol, the isocyanate compound is 1 to 15 moles, and the unsaturated chain extender is 0.01 to 15 moles; preferably, based on 1 mole of the macromolecular polyol, the isocyanate compound is 1.3 to 6.5 moles, and the unsaturated chain extender is 0.3 to 5.5 moles.
[0027] In the preparation method of the above polyurethane:
[0028] The macromolecular polyol is pre-treated to remove water, for example, removing water for 2 hours at 110°C, -0.05MPa, and 150rpm stirring conditions;
[0029] The conditions of the prepolymerization reaction in the method 1 are: the prepolymerization reaction temperature is 80-100° C., and the prepolymerization reaction time is 1-5 hours;
[0030] The conditions of the chain extension reaction in the method 1 are: the chain extension reaction temperature is 80-100° C., and the chain extension reaction time is 5-60 min;
[0031] The reaction conditions in the second method are: reaction temperature is 60-80°C, reaction time is 0.05-1h;
[0032] The curing conditions in the method 1 or the method 2 are: the curing temperature is 100 to 120° C., and the curing time is 6 to 24 hours.
[0033] The preparation method of the polysulfide containing dynamic bonds comprises: stirring an aldehyde compound and a polythiol compound for reaction at 70 to 100° C. and a protective gas atmosphere (such as nitrogen) for 20 to 60 minutes. Preferably, the molar ratio of the aldehyde compound to the polythiol compound is 1:4, wherein the aldehyde compound is calculated based on the molar number of aldehyde groups, and the polythiol compound is calculated based on the molar number of thiol groups.
[0034] The present invention adopts a one-step method or a two-step method (prepolymer method) to first prepare a polyurethane elastomer, and then obtains a high-toughness polylactic acid composite material containing dynamic bonds by dynamic vulcanization in high-temperature melt blending. By adjusting the polyurethane composition (for example: type and molecular weight of polyol, hard segment content), crosslinking agent structure type, polyurethane dosage, crosslinking agent dosage and other parameters, the obtained polylactic acid composite material has a notched impact strength of up to 99.38KJ / m 2 At the same time, the presence of dynamic bonds significantly reduces the shrinkage of the composite material, which is beneficial for precise processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The complex viscosity-angular frequency curves of Comparative Example 1, Comparative Example 3 and Example 2. DETAILED DESCRIPTION
[0036] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0037] The test instruments and test conditions used in the examples are as follows:
[0038] Notched impact strength test: refer to GB / T 1843-2008 for testing, and the instrument used is a cantilever beam impact testing machine.
[0039] Shrinkage test: Compare the actual area D2 and the mold area D1 of the notched impact specimen after injection molding. Shrinkage = (D1-D2) / D1*100%.
[0040] Complex viscosity test: Use a rotational rheometer at 180°C, 1% strain, 25mm parallel plate size, 1mm gap, test complex viscosity values in the range of 0.1rad / s to 100rad / s, and take 30 points.
[0041] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0042] Comparative Example 1
[0043] The dried polylactic acid was added into an internal mixer and melt-treated at 180° C. and 100 rpm for 6 minutes; and melt-mixed at 150 rpm for 15 minutes before being taken out.
[0044] Comparative Example 2
[0045] Preparation of polyurethane
[0046] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (1.63 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, and then unsaturated chain extender α-allyl glycerol ether (0.63 mol) was added and stirred rapidly for 25 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours. The designed polyurethane hard segment content is 25 wt%, the R value is 1, and the sample is referred to as MPU-1.
[0047] Preparation of polylactic acid composite materials
[0048] The dried polylactic acid (75wt%) was added into an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane MPU-1 (25wt%) was added into an internal mixer and melt-mixed at 100 rpm for 3 minutes; and the mixture was taken out after melt-mixing at 150 rpm for 15 minutes.
[0049] Comparative Example 3
[0050] Preparation of polylactic acid composite materials
[0051] The dried polylactic acid (75wt%) was added to an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes; the cured and dried polyurethane MPU-1 (25wt%, prepared by the same method as in Comparative Example 2) was added to an internal mixer and melt-mixed for 3 minutes at 100 rpm; 0.3wt% of diisopropyl peroxide as a free radical initiator was added and melt-mixed at 150 rpm for 15 minutes before being taken out.
[0052] Example 1
[0053] Preparation of cross-linking agents containing dynamic bonds
[0054] Benzaldehyde (1 mol) and ethanedithiol (2 mol) were stirred and reacted at 80° C. under a nitrogen atmosphere for 30 min to obtain a cross-linking agent 2,2-((phenylmethylene)bis(sulfinyl)dithiol), which was recorded as cross-linking agent C.
[0055] Preparation of polylactic acid composite materials
[0056] The dried polylactic acid (93 wt%) was added to an internal mixer and melt-treated at 170°C and 50 rpm for 2 minutes. The cured and dried polyurethane MPU-1 (7 wt%, prepared by the same method as in Comparative Example 2) was added to an internal mixer and melt-mixed for 2 minutes at 50 rpm. 0.15 wt% of a crosslinking agent C (based on the total weight of the polylactic acid and the polyurethane) was added and melt-mixed at 100 rpm for 5 minutes before removal.
[0057] Example 2
[0058] Preparation of polylactic acid composite materials
[0059] The dried polylactic acid (75 wt%) was added to an internal mixer and melt-treated at 180°C and 100 rpm for 3 minutes. The cured and dried polyurethane MPU-1 (25 wt%, prepared by the same method as in Comparative Example 2) was added to the internal mixer and melt-mixed for 3 minutes at 100 rpm. 0.3 wt% of the crosslinking agent C (based on the total weight of the polylactic acid and the polyurethane) was added and melt-mixed at 150 rpm for 15 minutes before being taken out.
[0060] Example 3
[0061] Preparation of polylactic acid composite materials
[0062] The dried polylactic acid (50 wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes. The cured and dried polyurethane MPU-1 (50 wt%, prepared by the same method as in Comparative Example 2) was added to an internal mixer and melt-mixed for 5 minutes at 200 rpm. 2 wt% of the crosslinking agent C (based on the total weight of the polylactic acid and the polyurethane) was added and melt-mixed at 200 rpm for 25 minutes before being taken out.
[0063] Example 4
[0064] Preparation of polyurethane
[0065] Polytrimethylene ether glycol (1 mol, number average molecular weight of 1000) was dehydrated for 2 hours at 110°C, -0.05 MPa, 150 rpm stirring conditions, and the dehydrated polytrimethylene ether glycol, pentamethylene diisocyanate (3.95 mol), catalyst dibutyltin dilaurate (0.03 wt%), and antioxidant anti-1010 (0.03 wt%) were prepolymerized at 90°C for 3 hours, and then unsaturated chain extender α-allyl glycerol ether (2.95 mol) was added and stirred rapidly for 10 minutes, and the polyurethane sample was taken out and cured in an oven at 100°C for 12 hours. The obtained polyurethane hard segment content was 50 wt%, and the sample was referred to as MPU-2.
[0066] Preparation of polylactic acid composite materials
[0067] The dried polylactic acid (50 wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes; the cured and dried polyurethane MPU-2 (50 wt%) was added to the internal mixer and melt-mixed at 200 rpm for 5 minutes; 0.01 wt% of crosslinking agent C (based on the total weight of polylactic acid and polyurethane) was added, and the mixture was melt-mixed at 200 rpm for 25 minutes before being taken out.
[0068] Example 5
[0069] Preparation of polylactic acid composite materials
[0070] The dried polylactic acid (50 wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes. The cured and dried polyurethane MPU-2 (50 wt%, prepared by the same method as in Example 4) was added to an internal mixer and melt-mixed at 200 rpm for 5 minutes. 4 wt% of the crosslinking agent C (based on the total weight of the polylactic acid and the polyurethane) was added and melt-mixed at 200 rpm for 25 minutes before being taken out.
[0071] Example 6
[0072] Preparation of polylactic acid composite materials
[0073] The dried polylactic acid (50 wt%) was added to an internal mixer and melt-treated at 200° C., 200 rpm for 5 minutes. The cured and dried polyurethane MPU-2 (50 wt%, prepared by the same method as in Example 4) was added to an internal mixer and melt-mixed at 200 rpm for 5 minutes. 7 wt% of the crosslinking agent C (based on the total weight of the polylactic acid and the polyurethane) was added and melt-mixed at 200 rpm for 25 minutes before being taken out.
[0074] Example 7
[0075] Preparation of polylactic acid composite materials
[0076] The dried polylactic acid (50wt%) was added to an internal mixer and melt-treated at 200°C, 200 rpm for 5 minutes; the cured and dried polyurethane MPU-2 (50wt%, prepared by the same method as in Example 4) was added to an internal mixer and melt-mixed at 200 rpm for 5 minutes; 10wt% of crosslinking agent C (based on the total weight of polylactic acid and polyurethane) was added, and the mixture was melt-mixed at 200 rpm for 25 minutes before being taken out.
[0077] Example 8
[0078] Preparation of polylactic acid composite materials
[0079] The dried polylactic acid (90 wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes; the cured and dried polyurethane MPU-1 (10 wt%, prepared by the same method as in Comparative Example 2) was added to the internal mixer and melt-mixed for 5 minutes at 200 rpm; 0.15 wt% of the crosslinking agent 2,2'-difuranmethane (based on the total weight of the polylactic acid and the polyurethane) was added, and the mixture was melt-mixed at 200 rpm for 25 minutes before being taken out.
[0080] Example 9
[0081] Preparation of polylactic acid composite materials
[0082] The dried polylactic acid (85wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes; the cured and dried polyurethane MPU-1 (15wt%, prepared by the same method as in Comparative Example 2) was added to the internal mixer and melt-mixed for 5 minutes at 200 rpm; 0.2wt% of the crosslinking agent 2,2'-difuranmethane (based on the total weight of the polylactic acid and the polyurethane) was added, and the mixture was melt-mixed at 200 rpm for 25 minutes before being taken out.
[0083] Example 10
[0084] Preparation of polylactic acid composite materials
[0085] The dried polylactic acid (75wt%) was added to an internal mixer and melt-treated at 200°C and 200 rpm for 5 minutes; the cured and dried polyurethane MPU-1 (25wt%, prepared by the same method as in Comparative Example 2) was added to the internal mixer and melt-mixed for 5 minutes at 200 rpm; 0.3wt% of the crosslinking agent 2,2'-difuranmethane (based on the total weight of the polylactic acid and the polyurethane) was added, and the mixture was melt-mixed at 200 rpm for 25 minutes before being taken out.
[0086] The polyurethane composite materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were tested for notched impact strength. The test results are shown in Table 1.
[0087] Table 1. Summary of notched impact strength data
[0088] <![CDATA[Notched impact strength (KJ / m 2 )]]> Shrinkage rate (%) Comparative Example 1 3.15 0.71 Comparative Example 2 13.42 0.75 Comparative Example 3 56.26 10.45 Example 1 15.32 0.85 Example 2 58.56 0.83 Example 3 80.64 0.96 Example 4 45.38 0.79 Example 5 85.69 1.06 Example 6 95.45 1.23 Example 7 99.38 1.47 Example 8 30.43 0.80 Example 9 43.29 0.82 Example 10 56.82 0.89
[0089] Comparative Example 1 is pure polylactic acid, Comparative Example 2 is a polylactic acid / MPU composite material, and Comparative Example 3 is a polylactic acid / MPU composite material using a free radical initiator to form a cross-linked polyurethane structure, and its impact strength is significantly improved.
[0090] It can be seen from the test results in Table 1 that the toughness of the prepared polylactic acid composite material is significantly improved by adjusting the polyurethane composition, polyurethane filling amount, cross-linking agent structure and dosage in Examples 1 to 10 of the present invention. At the same time, since the polylactic acid / MPU composite material in the present invention contains a dynamic bond structure, the internal stress and shrinkage deformation phenomenon can be reduced through dynamic bond exchange, so that the dimensional shrinkage rate during processing is significantly reduced and close to the level of pure polylactic acid.
[0091] In addition, by Figure 1 It can be seen from the curve in that, at the same polyurethane filling amount, the complex viscosity of Example 2 with dynamic bonds is significantly lower than that of Comparative Example 3 without dynamic bonds, and is close to that of pure polylactic acid, which is beneficial to reducing dimensional shrinkage during processing and maintaining dimensional stability of the product.
Claims
1. A low shrinkage and high toughness polylactic acid composite material, comprising: The reaction product of polylactic acid, polyurethane and a crosslinking agent, wherein the crosslinking agent is at least one of a polysulfide containing a dynamic bond and a compound containing a polyfuran group, the polysulfide containing a dynamic bond is the reaction product of an aldehyde compound and a polythiol compound, and the compound containing a polyfuran group is selected from at least one of 2,2'-difuranmethane and 2,2'-(1,3-propylenediyl)difuran; and the polyurethane is the reaction product of a macromolecular polyol, an isocyanate compound and an unsaturated chain extender.
2. The polylactic acid composite material according to claim 1, characterized in that: In the polyurethane, the hard segment content is 10-50wt%; and / or, Based on 100wt% of the total amount of the high-toughness polylactic acid composite material, the content of the polyurethane is 5-50wt%; and / or, Based on the total amount of the polylactic acid and the polyurethane being 100wt%, the amount of the crosslinking agent used is 0.01-12wt%.
3. The polylactic acid composite material according to claim 2, characterized in that: In the polyurethane, the hard segment content is 20-30wt%; and / or, Taking the total amount of the high-toughness polylactic acid composite material as 100wt%, the content of the polyurethane is 10-50wt%; and / or, Based on the total amount of the polylactic acid and the polyurethane being 100wt%, the amount of the crosslinking agent is 0.15-10wt%.
4. The polylactic acid composite material according to claim 1, characterized in that: The aldehyde compound is selected from at least one of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, succinaldehyde, terephthalaldehyde, and trimesic acid; and / or, The polythiol compound is at least one selected from ethanedithiol, propylenethiol, butanedithiol, 1,2,4,5-tetramercaptobenzene, pentaerythritol tetrakis(2-mercaptoacetic acid), pentaerythritol tetrakis(3-mercaptopropionic acid), and hexamercaptotriphenylene; and / or, The macromolecular polyol is selected from at least one of polyester polyol, polyether polyol, polyolefin polyol, polysiloxane polyol, or derivatives thereof; and / or, The number average molecular weight of the macromolecular polyol is 500-4000; and / or, The isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, isophorone diisocyanate, dimethyl biphenyl diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, norbornane diisocyanate, methylcyclohexyl diisocyanate, pentamethylene diisocyanate, lysine diisocyanate, polymethylene polyphenyl isocyanate, and toluene diisocyanate dimer; and / or, The unsaturated chain extender is selected from at least one of small molecule diols with unsaturated carbon-carbon double bonds; and / or, Antioxidant is also added into the polyurethane.
5. The polylactic acid composite material according to claim 4, characterized in that: The macromolecular polyol is selected from at least one of polycaprolactone, polypropylene glycol, polyethylene glycol, polybutylene adipate, polypropylene adipate, polyethylene adipate, polypropylene succinate, polyethylene succinate, polytetrahydrofuran, polytrimethylene ether glycol, hydroxy-terminated butylbenzene polyol, hydroxy-terminated butadiene polyol, polyfarnesene polyol, and polysiloxane polyol; and / or, The number average molecular weight of the macromolecular polyol is 1000-2000; and / or, The isocyanate compound is selected from at least one of pentamethylene diisocyanate and hexamethylene diisocyanate; and / or, The unsaturated chain extender is selected from at least one of α-allyl glyceryl ether and trimethylolpropane monoallyl ether; and / or, The antioxidant is selected from at least one of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.
6. A method for preparing the low shrinkage and high toughness polylactic acid composite material according to any one of claims 1 to 5, comprising: The polylactic acid is melted and added to the polyurethane and mixed evenly, and a cross-linking agent is added and melt-blended to obtain the polylactic acid composite material with low shrinkage and high toughness.
7. The preparation method according to claim 6, characterized in that: The conditions of the melt blending are: a melting temperature of 165-200° C. and a melting time of 5-30 min.
8. The preparation method according to claim 6, characterized in that: The polyurethane is prepared by the following method: Method 1: Prepolymerize a macromolecular polyol and an isocyanate compound under the action of a catalyst, then add an unsaturated chain extender to carry out a chain extension reaction, and obtain the polyurethane after curing; or, Method 2: stirring and reacting a macromolecular polyol, an isocyanate compound and an unsaturated chain extender under the action of a catalyst, and curing the resultant to obtain the polyurethane.
9. The preparation method according to claim 8, characterized in that: The catalyst is selected from at least one of an organic tin catalyst, an organic zinc catalyst, and an organic bismuth catalyst; and / or, The amount of the catalyst is 0.01-0.5wt% of the total amount of the macromolecular polyol, isocyanate compound and unsaturated chain extender; and / or, An antioxidant is also added to the reaction; and / or, Based on 1 mole of the macromolecular polyol, the isocyanate compound is 1 to 15 moles, and the unsaturated chain extender is 0.01 to 15 moles.
10. The preparation method according to claim 9, characterized in that: The catalyst is selected from at least one of stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, di(dodecylthio)dibutyltin, zinc isooctanoate, and bismuth isooctanoate; and / or, The amount of the antioxidant is 0.01-0.5wt% of the total amount of the macromolecular polyol, isocyanate compound and chain extender; and / or, Based on 1 mole of the macromolecular polyol, the isocyanate compound is 1.3 to 6.5 moles, and the unsaturated chain extender is 0.3 to 5.5 moles.
11. The preparation method according to claim 8, characterized in that: The conditions of the prepolymerization reaction in the method 1 are: the prepolymerization reaction temperature is 80-100° C., and the prepolymerization reaction time is 1-5 hours; and / or, The conditions of the chain extension reaction in the method 1 are: the chain extension reaction temperature is 80-100° C., and the chain extension reaction time is 5-60 min; and / or, The reaction conditions in the second method are: reaction temperature is 60-80°C, reaction time is 0.05-1h; and / or, The curing conditions in the method 1 or the method 2 are: the curing temperature is 100-120° C., and the curing time is 6-24 hours.
12. The preparation method according to claim 6, characterized in that: The preparation method of the polysulfide containing dynamic bonds comprises: stirring an aldehyde compound and a polythiol compound at 70-100° C. and reacting them for 20-60 minutes in a protective gas atmosphere.
13. The preparation method according to claim 12, characterized in that: The molar ratio of the aldehyde compound to the polythiol compound is 1:4, wherein the aldehyde compound is calculated based on the molar number of aldehyde groups, and the polythiol compound is calculated based on the molar number of thiol groups.
Citation Information
Patent Citations
High-toughness polylactic acid / crosslinked polyurethane compound and preparation method thereof
CN103450649A
Rigidity-toughness balanced super-toughness polylactic acid-based nano composite material and preparation method thereof
CN107459793A
Vegetable oil derivative reactive blending method for preparing high-impacting toughness polylactic acid compound
CN108707322A
High-toughness bio-based polylactic acid / reactive modified rubber thermoplastic vulcanized rubber blending material and secondary reaction extrusion preparation method thereof
CN109401243A
Toughened modified polylactic acid plastic and preparation method thereof
CN114507424A